Effect of Chicken Intestine Substitution to Chemical Quality of Nugget - Harapin Hafid; Nuraini Nuraini; Dian Agustina; Fitrianingsih Fitrianingsih; Inderawati Inderawati (Animal Production: Indonesian Journal of Animal Production, 2017)
This research was aimed to study the chemical quality of the chicken nuggets substituted chicken intestine. The treatment was substitution of chicken meat with chicken intestine consisting of five levels was A0 (0% chicken intestine + 100% chicken meat), A1 (15% chicken intestine + 85% chicken meat), A2 (25% chicken intestine + 75% chicken meat ), A3 (40% chicken intestine + 60% chicken meat), A4 (50% chicken intestine + 50% chicken meat), A5 (65% chicken intestine + 35% chicken meat), A6 (75% chicken intestine + 25% chicken meat), A7 (90% chicken intestine + 10% chicken meat), and A8 (100% chicken intestine + 0% chicken meat). Each treatment was repeated five times. The results showed that the water content and ash substituted chicken nuggets chicken intestines were not significantly different (p> 0.05). water content of chicken nuggets  in this study was A0 (99.8%), A1 (99.8%), A2 (99.8%), A3 (99.8%), A4 (99.8%), A5 (99.9%), A6 (99.9%), A7 (99.7%), and A8 (99.8%). Ash content on A0 (2.61%), A1 (1.61%), A2 (2.90%), A3 (1.80%), A4 (2.23%), A5 (2.84% ), A6 (2.62%), A7 (2.39%), and A8 (2.26%). Intestine substitution into the chicken nuggets significant (p <0, 05) against the protein and fat content of chicken nuggets, where the highest protein content in treatment A8 (100% chicken intestine) was 24.9% and the lowest in treatment A0 (100% chicken meat) that is 11.33%. The greater increase in the nugget chicken intestinal waste, the higher the protein content. Meanwhile nugget fat content tends to decrease as the percentage of the addition of chicken intestinal waste. Fat content nuggets with chicken intestinal waste substitution of 15% (A1) amounted to 21.85%   , 25% (A2) of 20.56% , 40% (A3) of 19.09%, 50% (A4) of 18.14, 65% (A5) of 17.03%, 75% (A6) of 15.69%, 90% (A7) of 14.11%, and 100% (A8) 11.00% house-cleaning da significantly (p <0.05) with control of 0% (A0) 23.93%. The more the addition of substitution intestinal produce low-fat nugget. Can be concluded that substitution of chicken intestine increase the protein and lower fat content of chicken nuggets. Nugget product with composition 50% chicken intestine and 50% chicken meat (A4) has water content 99,8%, 17,58%, protein, 18,14% abu2.23% fat and preferred by the panelists.